Analyzing Factors Influencing Subscription Decisions for Exclusive Content on Instagram - Khair, Muhammad Syafwan (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study examines the impact of service quality, price, and electronic word of mouth (e-WOM) on purchasing decisions for subscribing to exclusive influencer content on Instagram, with user satisfaction serving as a mediating variable. Utilizing a quantitative explanatory approach, data were collected from 101 active Instagram users in Indonesia, aged 17-40, who have previously subscribed to exclusive content. Structural Equation Modeling (SEM) with SmartPLS 4 software was employed to analyze the direct and indirect relationships between variables. The findings reveal that service quality significantly influences both purchasing decisions and user satisfaction, indicating that users are more likely to subscribe and feel satisfied when the platform is reliable and easy to use. Price also positively affects purchasing decisions and satisfaction, demonstrating that competitive pricing enhances users’ willingness to subscribe and satisfaction with the service. Although e-WOM directly impacts user satisfaction, it does not significantly influence purchasing decisions, either directly or through the mediating variable. User satisfaction emerges as a key mediator, with satisfied users being more inclined to make or continue subscriptions. These results highlight the importance of improving platform service quality and pricing strategies while leveraging e-WOM to boost user satisfaction and indirectly influence purchasing decisions. This study provides valuable insights for businesses implementing subscription models on social media platforms.